2017
DOI: 10.1016/j.cmi.2017.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Added diagnostic value and impact on antimicrobial therapy of 16S rRNA PCR and amplicon sequencing on resected heart valves in infective endocarditis: a prospective cohort study

Abstract: The very good performance characteristics, added diagnostic value and impact on antimicrobial therapy of molecular testing of heart valves should support the incorporation of molecular testing in diagnostic criteria and guidelines for IE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 16 publications
3
13
2
2
Order By: Relevance
“…Effect of pre-operative antibiotic treatment on valve cultures is controversial, as two studies found no effect [6, 11], but two reported a negative effect [7, 9]. In our material, we had no positive valve cultures after 2 weeks of antimicrobial treatment.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…Effect of pre-operative antibiotic treatment on valve cultures is controversial, as two studies found no effect [6, 11], but two reported a negative effect [7, 9]. In our material, we had no positive valve cultures after 2 weeks of antimicrobial treatment.…”
Section: Discussionmentioning
confidence: 57%
“…In a study by Peeters et al most (19/24) patients had a causative agent detected with 16S rRNA PCR even after 21 days of antibiotic therapy [6] and another study could not confirm any correlation between the length of pre-operative antibiotic treatment and positive PCR results [9]. Rovery et al demonstrated that bacterial DNA may persist in heart valves for a long time after successful treatment and does not necessarily represent viable organisms [8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Up to 30% of samples from these patients are culture-negative, mostly due to the presence of atypical microorganisms and/or antimicrobial use [19]. Peeters et al found that the sensitivity of 16S rRNA PCR (87%) was much higher than that of valve culture (26%) and suggested that the molecular approach was particularly useful for patients with culture-negative infective endocarditis [24]. In our study group, especially for patient 116, 16S rRNA PCR was the most important diagnostic tool for B. quintana, an agent of culture-negative infective endocarditis.…”
Section: Discussionmentioning
confidence: 99%